Analysis of Women's Representation in Indonesian Films - Putri, Siti Aminah (Enigma Institute, 2023)
Film is a mass media that has a strong influence in shaping public perception. Representation of women in films can reflect the values and social norms that apply in society. This research aims to analyze the representation of women in Indonesian films. The method used is Roland Barthes' semiotic analysis model. Research data was obtained from three Indonesian films, namely